The effect of hyperbaric oxygenation therapy on myocardial function - Leitman, Marina; Efrati, Shai; Fuchs, Shmuel; Hadanny, Amir; Vered, Zvi (The International Journal of Cardiovascular Imaging, 2020)
Hyperbaric oxygenation therapy is successfully implemented for the treatment of several disorders. Data on the effect of hyperbaric oxygenation on echocardiographic parameters in asymptomatic patients is limited. The current study sought to evaluate the effect of hyperbaric oxygenation therapy on echocardiographic parameters in asymptomatic patients. Thirty-one consecutive patients underwent a 60-sessions course of hyperbaric oxygenation therapy in an attempt to improve cognitive impairment. In all subjects, echocardiography examination was performed before and after a course of hyperbaric oxygenation therapy. Conventional and speckle tracking imaging parameters were calculated and analyzed. The mean age was 70 ± 9.5 years, 28 [90%] were males. History of coronary artery disease was present in 12 [39%]. 94% suffered from hypertension, 42% had diabetes mellitus. Baseline wall motion abnormalities were found in eight patients, however, global ejection fraction was within normal limits. During the study, ejection fraction [EF], increased from 60.71 ± 6.02 to 62.29 ± 5.19%, p = 0.02. Left ventricular end systolic volume [LVESV], decreased from 38.08 ± 13.30 to 35.39 ± 13.32 ml, p = 0.01. Myocardial performance index [MPi] improved, from 0.29 ± 0.07 to 0.26 ± 0.08, p = 0.03. Left ventricular [LV] global longitudinal strain increased from − 19.31 ± 3.17% to − 20.16 ± 3.34%, p = 0.036 due to improvement in regional strain in the apical and antero-septal segments. Twist increased from 18.32 ± 6.61° to 23.12 ± 6.35° p = 0.01, due to improvement in the apical rotation, from 11.76 ± 4.40° to 16.10 ± 5.56°, p = 0.004. Hyperbaric oxygen therapy appears to improve left ventricular function, especially in the apical segments, and is associated with better cardiac performance. If our results are confirmed in further studies, HBOT can be used in many patients with heart failure and systolic dysfunction.